Safety and efficacy of a novel balloon colonoscope: a prospective cohort study - Gralnek, Ian M.; Suissa, Alain; Domanov, Sveta (Endoscopy, 2014)
Background and study aims: Although colonoscopy is the gold standard for detecting colorectal cancer (CRC), adenomas and cancers are missed. We aimed to establish the safety and feasibility of use of a novel balloon-colonoscope.Patients and methods: Patients (40 – 75 years) referred for CRC screening, polyp surveillance, or diagnostic evaluation were enrolled in a prospective pilot cohort study whose primary endpoint was device safety. Additional endpoints included success of and time to cecal intubation, withdrawal and total procedure times, polyp detection rate (PDR), adenoma detection rate (ADR), and success of polypectomies.Results: Among 50 patients (mean age 59.0 years, 27 women [54 %]), three were excluded (inadequate colon preparation, technical problem, abdominal hernia) and 47 were analyzed. Two patients experienced minor adverse events (diarrhea, abdominal pain). Cecal intubation rate was 47 /47 (100 %). Mean times, to reach cecum, withdrawal, and total procedure, were 4.3, 7.4, and 16.5 minutes, respectively. We identified 44 polyps (all successfully removed) in 25 /47 patients (PDR 53.2 %), 35 polyps (79.5 %) were 1 – 5 mm, 4 (9.1 %) 6 – 9 mm, and 5 (11.4 %) ≥ 10 mm. Of 44 polyps, 36 (81.8 %) were “adenomas”; 21/47 patients had ≥ 1 adenoma (ADR 44.7 %).Conclusions: The NaviAid G-EYE balloon-colonoscope appears safe and feasible to use. Comparative human studies are underway.Clinicaltrials.gov identifier: NCT01749722